Gender and age differences in weekend eating habits: associations with fat mass percentage in a cross-sectional study - Gorini, Stefania; Camajani, Elisabetta; Feraco, Alessandra; Armani, Andrea; Quattrini, Chiara; Tarsitano, Maria Grazia; Cava, Edda; Di Renzo, Laura; Caprio, Massimiliano; De Lorenzo, Antonino; Lombardo, Mauro (Frontiers in Nutrition, 2025)
IntroductionWeekend eating habits are often different from those of weekdays, but their impact on body composition remains little explored. This study investigates gender and age differences in weekend eating behaviors and their association with fat mass percentage (FM%).MethodsA cross-sectional study was conducted on 2,596 participants at an obesity center in Italy. Eating habits were assessed with a self-reported questionnaire, classifying weekend eating behavior into four categories: maintaining weekday eating patterns, cooking at home, eating out, and eating prepared meals. Weekday eating was considered the participant’s habitual eating pattern as reported during clinical evaluation. Differences in FM% between groups were analyzed by ANOVA and the influence of gender and age was examined by multiple linear regression models.ResultsSignificant differences between gender and age were observed specifically in weekend eating behaviors (p < 0.001). Women were significantly more likely to cook at home, whereas men, particularly those aged 18–30 years, were more likely to eat out. Women who cooked at home during the weekend had a higher FM% than those who ate out or maintained weekday eating habits (p < 0.001) but consistency alone does not guarantee better body composition, as the quality of the diet was not assessed. Among men aged 31–45 years, cooking at home was associated with a higher FM% than maintaining weekday habits (p = 0.0028). Regression analysis showed that FM% was higher in females and older age groups, while eating out, being hosted, or maintaining weekday habits were associated with lower FM% compared to cooking at home (all p < 0.05).ConclusionWeekend eating habits represent a distinct and influential factor on body composition, rather than a simple extension of weekday patterns. The results emphasize that gender- and age-specific approaches are crucial in dietary interventions, particularly for younger men and women who maintain structured meal patterns. These results suggest that weekends may be an important period for dietary interventions based on self-reported dietary patterns, with potential implications for gender- and age-specific dietary interventions and broader public health strategies aimed at improving long-term metabolic outcomes.